Comparative Study of the Use of Hydraulic Pile Driver and Crane Mounted Drop Hammer in the Piling of Precast Prestressed Concrete Piles for Building Foundations in Kubu Raya Regency - Syahrudin, Syahrudin; Nuh, Safarudin M; Michelim, Albert Stanley (Jurnal Teknik Sipil, 2022)
Most of the soil conditions in Kubu Raya Regency are soft and peat soil with low carrying capacity and the potential for foundation subsidence, especially in high-rise buildings. Using a Hydraulic Static Pile Driver with a capacity of 120 tons and a Crane Mounted Drop Hammer with a capacity of 35 tons is an alternative to driving deep foundations on soft/peat soils. The purpose of this study was to conduct a comparative study of productivity, costs, risk aspects, occupational safety and health and environmental impacts of the two tools in the work of 30x30 cm precast concrete piles on the foundations of high-rise buildings in Kubu Raya Regency.